New relationships among science, philosophy and religious studies - Drago, Antonino (Rivista Italiana di Filosofia del Linguaggio, 2023)
In past times some religious studies built deductive theories managed by classical logic. On the basis of recent interpretations of Nicholas Cusanus’ philosophical and logical thought it is shown that religious studies also can consistently use non-classical logic (intuitionist and modal ones). It was proved that through the intuitionist logic the main Christian teachings (enemy’s love, Beatitudes, original sin) acquire full, rational meanings and that the main two dogmas of Christian faith result not only without contradictions but also perfectly rational. In this light it is no longer true that sciences are the only rational studies and religious studies are based on imagination, intuition, analogy, and metaphor; both can distinguish within their use of natural language at least two different logics, the classical and the intuitionist, and moreover they can rigorously reason. In addition, again in the wake of Cusanus, the dichotomy between actual infinity and potential infinity is recognized important for the Abrahamic religious studies, which always well-distinguish them as belonging respectively and distinctly to God and to man. Since half a century this dichotomy was formalized in two different formulations of the entire mathematics, the classical and the constructive formulation. Consequently, in religious studies there exist two dichotomies, which also turn out to be the foundations of the natural sciences and (according to Leibniz) of the activity of human reason. Then the interdisciplinary comparison between science, philosophy and religious studies is much more rich and fruitful than in past times, because it takes into account that 1) the foundations of both are pluralist and 2) the latter ones can also be well-formalized according to both logic and mathematics.